Persepsi Wisatawan Terhadap Daya Tarik Wisata Monumen Perjuangan Rakyat Bali - Dewi, Ni Ketut Ari Cahya; Bhaskara, Gde Indra (JURNAL DESTINASI PARIWISATA; Vol 11 No 2 (2023): VOL 11, NO 2 (2023): (JULY-DECEMBER) JURNAL DESTINASI PARIWISATA, 2023)
The monument is one of the tourist attractions that have historical and cultural values that should be preserved. Monumen Perjuangan Rakyat Bali is one of the old monuments located in Denpasar City and become an icon of a blend of historical and cultural tourism. The purpose of this study to determine the tourist perceptions of tourist attraction to Monumen Perjuangan Rakyat Bali. This study uses a descriptive analysis method with a qualitative approach. The data used are primary data and secondary data with data collection techniques used observation, interviews, questionnaires, and documentation. Determination of the sample is calculated using the Slovin formula with a special sampling technique for 100 respondents. The results of this study indicate that the perceptions of tourists to Monumen Perjuangan Rakyat Bali shows a good response, because from the analysis of the 19 variables measured to obtain positive responses. Even so, suggestions that can be given are the need to increase the numer of toilets, provide facilities for persons with disabilities, and increase security in the monument parking area so that visiting tourists can feel comfortable and safe while at the Monumen Perjuangan Rakyat Bali. The variable that was stated to be quite good was the cleanliness of the area and pool. In particular, cleanliness in monument pools needs to be improved because cleanliness is still lacking so that the pool water looks mossy and is not good to look at. With a clean tourist attraction, it certainly creates a beautiful situation that can provide a deep message for visiting tourists. Therefore, cleanliness is the main thing in a tourist attraction. Keywords: Tourist Perceptions, Toursit Attraction, Monumen Perjuangan Rakyat Bali